Simbol dan Makna dalam Prosesi Ritual Mematua pada To Kaili - Sasmita, Susi; Dewi, Citra; Nasrum, Muh.; Hendra, Hendra; Badollahi, Muh. Zainuddin (CV. Social Politic Genius (SIGn), 2022)
This research aims to understand the symbols and meanings of the Mematua ritual procession among the Kaili indigenous people in Siniu Sayogindano Village. This research uses an ethnographic analysis. Ethnographic analysis is an approach that begins with field facts, analyzes them based on cultural theories and relevant arguments to explore the cultural situation of the community, and ultimately yields a conclusion. The results show that the Mematua ritual procession among the Kaili indigenous people is an event rich in symbols and meanings, embodying deep cultural values and reflecting local wisdom. The eight stages of this procession, from the Polele fetching the bride to both newlyweds seeking blessings from their parents, not only represent steps in a wedding ritual but also teach the importance of harmony, respect, and commitment in marital life. Each aspect of the Mematua ritual reflects harmony among individuals, families, and the broader indigenous community. This underscores that marriage in the Kaili indigenous tradition is an event uniting two individuals and a community ritual involving respect for social and spiritual values passed down through generations. Therefore, it is recommended that the Department of Education and Culture of Parigi Moutong Regency intensify efforts to document and research the Mematua ritual procession of the Kaili indigenous people to ensure that the richness of symbols and meanings in this tradition is preserved and continues to be recognized by future generations. For the Kaili indigenous people, it is advised to continue nurturing and practicing this tradition, not only as a way to celebrate significant life moments but also as a means to strengthen community bonds and honor a rich cultural legacy. Greater involvement of the indigenous community in preparing and conducting this ritual procession can effectively preserve the social and spiritual values foundational to the Kaili tribe amidst the challenges of modernity and globalization.